2017
DOI: 10.1038/ncomms15549
|View full text |Cite
|
Sign up to set email alerts
|

Possible absence of critical thickness and size effect in ultrathin perovskite ferroelectric films

Abstract: Although the size effect in ferroelectric thin films has been known for long time, the underlying mechanism is not yet fully understood and whether or not there is a critical thickness below which the ferroelectricity vanishes is still under debate. Here, we directly measure the thickness-dependent polarization in ultrathin PbZr0.2Ti0.8O3 films via quantitative annular bright field imaging. We find that the polarization is significantly suppressed for films <10-unit cells thick (∼4 nm). However, approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 42 publications
3
92
0
Order By: Relevance
“…In a perovskite structure, the rigid oxygen octahedron exhibits various structural distortions driven by stain and electrostatic conditions, underpinning vast functionalities. Many efforts have been paid to precisely measure the local distortion in perovskite structures by various microscopy techniques [2-4, 26, 33-47] but not much in ABF-STEM imaging [13,14,29]. In our work, we use a probe corrected ARM300CF (JEOL Ltd.) microscope, operating at 300 kV, and we simultaneously record both ADF-and ABF-STEM images, where a convergence semi-angle is 24 mrad, detector collection semi-angles spanning from 65 to 200 mrad for ADF and 12 to 24 mrad for ABF imaging, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In a perovskite structure, the rigid oxygen octahedron exhibits various structural distortions driven by stain and electrostatic conditions, underpinning vast functionalities. Many efforts have been paid to precisely measure the local distortion in perovskite structures by various microscopy techniques [2-4, 26, 33-47] but not much in ABF-STEM imaging [13,14,29]. In our work, we use a probe corrected ARM300CF (JEOL Ltd.) microscope, operating at 300 kV, and we simultaneously record both ADF-and ABF-STEM images, where a convergence semi-angle is 24 mrad, detector collection semi-angles spanning from 65 to 200 mrad for ADF and 12 to 24 mrad for ABF imaging, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, atomic thickness ferroelectricity has been found in monolayer chalcogenides: M (1) X, M (2) X 2 , and M 2 (3) X 3 (M (1) = Ge, Sn; M (2) = Mo, W; M (3) = Al, Ga, In; X = S, Se, Te). Fortunately, more and more atomic thickness spontaneous electric polarization has been discovered in ionic compound monolayer with the puckered lattice structure.…”
Section: Doi: 101002/aelm201800475mentioning
confidence: 99%
“…[1][2][3] For typical perovskite ferroelectrics, BaTiO 3 and PbTiO 3 , ferroelectricity will vanish when the films thickness are reduced respectively to six unit cells (24 Å) [1] and three unit cells (12 Å). Overcoming the critical thickness effect will clear the way for the further miniaturization of ferroelectric devices, which have been attracting extensive research interest for many years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuth ferrite (BiFeO 3 ) is a prototypical room temperature multiferroic, and barium titanate (BaTiO 3 ) , on the other hand, is a ferroelectric . Previous study has shown that at some critical thickness (maximum thickness) in perovskite ferroelectric films, the localized enhancement of the electromagnetic field vanishes . The limit of the localized enhancement field in ultrathin film has been therefore established experimentally and theoretically and was found to be dependent on the material .…”
Section: Introductionmentioning
confidence: 99%